The Influence of Inflation, Interest Rates, Capital Structure, and Profitability on Stock Prices in Manufacturing Companies - Wulan Ramadhani; Deby Deby; Jesica Dara Tista (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of inflation, interest rates, capital structure, and profitability on stock prices in manufacturing companies. The background of this research highlights the volatility of the Indonesian economy, which is driven by macroeconomic factors that significantly affect capital market performance. Using the Systematic Literature Review (SLR) method, this study synthesized 10 relevant articles published between 2023 and 2025, collected through Google Scholar using specified keywords. The findings reveal varied results: inflation and interest rates generally have a negative influence on stock prices, although some studies report insignificant effects. Similarly, capital structure shows both positive and negative impacts, depending on company conditions and research contexts. Profitability also presents mixed outcomes; some studies found significant relationships, while others reported no influence on stock prices. This literature-based synthesis highlights inconsistencies in previous empirical findings and reinforces the need for further research to clarify the interaction between these variables and stock market performance. The study contributes to providing a comprehensive understanding for investors, financial analysts, and policymakers in making better investment and strategic financial decisions under uncertain economic conditions.